2017
DOI: 10.1103/physrevb.95.024113
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and piezoresistive properties of nickel carbides from first principles

Abstract: The nickel-carbon system has received increased attention over the past years due to the relevance of nickel as a catalyst for carbon nanotube and graphene growth, where Nickel carbide intermediates may be involved or carbide interface layers form in the end. Nickel-carbon composite thin films comprising Ni 3 C are especially interesting in mechanical sensing applications. Due to the metastability of nickel carbides, formation conditions and the coupling between mechanical and electrical properties are not yet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…The optimized lattice constant of bulk fcc Ni, 3.393 Å, is in accord with the experimental value of 3.52 Å . The optimized lattice constants of bulk cubic NiC, a = 4.047 Å, are also quite close to the reported theoretic value, a = 4.073 Å . The Ni(111) surface was modeled using a hexagonal p(2 × 2) supercell with four atomic layers separated by a vacuum with a depth of 15 Å.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The optimized lattice constant of bulk fcc Ni, 3.393 Å, is in accord with the experimental value of 3.52 Å . The optimized lattice constants of bulk cubic NiC, a = 4.047 Å, are also quite close to the reported theoretic value, a = 4.073 Å . The Ni(111) surface was modeled using a hexagonal p(2 × 2) supercell with four atomic layers separated by a vacuum with a depth of 15 Å.…”
Section: Methodssupporting
confidence: 80%
“…14 The optimized lattice constants of bulk cubic NiC, a = 4.047 Å, are also quite close to the reported theoretic value, a = 4.073 Å. 15 The Ni(111) surface was modeled using a hexagonal p(2 × 2) supercell with four atomic layers separated by a vacuum with a depth of 15 Å. The bottom two layers were fixed to their bulk positions, while the top two layers were allowed to fully relax.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Substantial efforts in nonequilibrium deposition techniques, such as sputter deposition, have enabled the controllable fabrication of nanocomposite thin films with thermodynamically metastable filler phases, such as metastable carbides (e.g., Ni 3 C). , These metastable filler phases can provide novel functionalities and are hard to obtain in a scalable manner with other deposition techniques. Also bottom-up self-organized nanoscale structuring of filler and matrix phases has been realized. …”
Section: Introductionmentioning
confidence: 99%
“…First MIC with LE experiments of amorphous carbon (a‐C) were reported by Konno and Sinclair . Following studies of MIC of a‐C focused on the synthesis of graphene by annealing Ni/a‐C bilayers, utilising the small lattice mismatch of nickel (111) and graphene (002) lattice planes and the low solubility of carbon in the nickel lattice . During these studies, models for the mechanisms behind the MIC of a‐C were suggested, employing Raman spectroscopy, electron microscopy and differential scanning calorimetry.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Following studies of MIC of a-C focused on the synthesis of graphene by annealing Ni/a-C bilayers, utilising the small lattice mismatch of nickel (111) and graphene (002) lattice planes and the low solubility of carbon in the nickel lattice. [8][9][10][11][12][13] During these studies, models for the mechanisms behind the MIC of a-C were suggested, employing Raman spectroscopy, electron microscopy and differential scanning calorimetry. In situ TEM and XRD studies gave insight into the processes during the MIC.…”
Section: Introductionmentioning
confidence: 99%